The surviving monozygotic twin. - Szymonowicz, W (1986)
It has been suggested that because of vascular interchange between the monozygous twins vascular disruptions from a deceased cotwin with disseminated intravascular coagulation causes embolisation in the surviving twin. This study reports six cases in which all the surviving monozygous twins had central nervous system infarcts and three had multiple organ infarcts, including pulmonary and hepatic infarcts, which have not been reported previously. Fetal death in utero occurred 1-11 weeks before the live birth of the monozygous survivor. In three cases there was pathological confirmation of a continuing process with infarcts ranging in age from a few days to eight weeks. Four infants died in the early neonatal period, and the remaining two survived with considerable handicap. A review of the published reports confirmed the high risk of vascular disruption affecting many organ systems and the extremely poor prognosis for subsequent death or handicap. We recommend that after detection of fetal death in utero in a suspected monozygous twin pregnancy careful consideration should be given to prompt delivery of the survivor and investigations should be carried out to rule out infarction in the central nervous system and other organs that are at risk.